A review on laser cladding of high-entropy alloys, their recent trends and potential applications. (August 2021) - Arif, Zia Ullah; Khalid, Muhammad Yasir; ur Rehman, Ehtsham; Ullah, Sibghat; Atif, Muhammad; Tariq, Ali
Abstract: High-Entropy Alloys (HEAs) are a promising class of metallic materials that have allured the world of material science and engineering. These intriguing materials are proving their worth in the coatings for severe ambient and demanding conditions. Laser cladding (LC) is a non-linear complex, multidisciplinary and modern technology applied for surface modification. Nobler properties of HEAs as compared to traditional alloys permitted the research community to explore Laser-Cladded High-Entropy Alloy Coatings (LC-HEACs) . Here, this article provides a review and recent trends of LC-HEACs, aiming to address the use of LC technology for HEA materials, the influence of process parameters on the geometric and metallurgical characteristics of the LC-HEACs. Common defects not limited to microcracks and residual stresses, and techniques to improve the quality of the LC-HEACs are elucidated. Furthermore, thermo-kinetics effect, thermomechanical behavior, microstructural evolution, and strengthening mechanisms are illustrated for a better understanding of laser-material interaction. The potential applications of the LC-HEACs are outlined considering wear, corrosion, erosion, and oxidation resistance and their corresponding substrates. The article also highlights the research gaps, current trends, and possible future directions in the context of critical challenges that need to be catered, before the actual implementation of LC-HEACs in industries. Owing to the variety of element constitution for HEAs design as well as excellent mechanical and functional properties, LC-HEACs will blossom in the years to come.